Severe floods predictive ability: A proxy based probabilistic assessment of the Italian early warning system - Francesco Silvestro; Luca Molini; Fausto Guzzetti; Federico Schiavi; Fabio Castelli; Luca Ferraris (Journal of Flood Risk Management)
Abstract In compliance with the national legal framework, the regional offices (CFDs) of the Italian Civil Protection Department have the daily duty to issue warnings to the local population on the account of the weather and hydrology‐related impacts, predicted by forecast models and refined through their expertise and experience: this composite of objective (model) and subjective (analyst) assessments are both contributing to the actual colour‐coded warning system. Given its hybrid nature, it is of paramount importance to evaluate the predictive ability of the warning decision‐making process as a whole. To this end, this study compares the return period T of the occurred flood (estimated through an hydrological model fed with observations) to the warning level that was issued. The novelty of this approach is that, by applying this methodology extensively in space and time, the probability curves of the variable T for each warning level are computed, allowing to evaluate the consistency between the warnings and the actual (estimated) severity of the event. As results suggest, the national early warning system is proven to be overall reliable for most cases, though very fine scale events (e.g., severe, localised, short‐lived thunderstorms) are still an open challenge.